Analysis of Psychological Factors and Free Shipping on Online Impulse Buying in Modest Fashion - Yusuf, Muhamad; Masnita, Yolanda; Yusran, Husna Leila (Manunggal Halim Jaya, 2026)
This research draws attention to impulsive buying behavior in a vibrant and booming modest fashion industry, one of the most significant contributor segments to e-commerce in Indonesia. Part of the difficulty is that consumers are increasingly making additional online impulsive purchases driven by psychological triggers and marketing efforts that prompt rapid, unplanned buying decisions. To investigate, the paper explores hedonic motivation, positive emotions, perceived trust, and online shopping attitude, along with free shipping, applying the Self-Determination Theory (SDT)- based model to the factors that incite impulsive purchase. Positive emotions and perceived trust are two of the most significant indicators (positive frailties) in standardized results for online impulse buying, with no direct effect from free shipping. Based on these findings, the study suggests that future research is needed to consider social cues and interface design factors to better understand impulse buying among MF consumers online and to develop marketing strategies that enhance the emotional experience.